¿ESTAMOS YA DENTRO DE UN NUEVO SISTEMA DE RESPONSABILIDAD DEL EMPLEADOR POR ACCIDENTES DE TRABAJO EN EL PERÚ? - Vásquez Concha, Jorge (Revista de Derecho, 2019)
There is no human activity without risks, especially at work. Therefore, employers should be interested to minimize risks in the workplace as is reasonable (obligation of means) instead of transferring the risks to workers. This kind of commitment is essential to fulfilling its obligation as a guarantor of the workers’ health and safety (obligation of result). Understanding this double duty is the key to solving many conflicts about employers’ liability for workplace accidents. It’s good to comply with the law, but it’s not enough. The legal is not necessarily the preventive, nor the ethical. In the prevention of occupational hazards, the law is the base, but not the optimal. We propose a new Employers’ Liability for Workplace Accidents System, of a quasi-objective type. This new System must be emancipated from the Civil Code rules on responsibility, foreseen for parties with equal autonomy. These Civil Code rules should no longer apply to labor relations between employers and workers, which are asymmetrical. Besides, this new System should develop a new Work Accident Insurance, universal and extensive to all economic activities of the country.
Keywords: employers’ liability for workplace accidents; workplace health and safety; duty to prevent occupational hazards; work accident compensation